Rhodol‐based far‐red fluorescent probe for the detection of cysteine and homocysteine over glutathione. (20th April 2016) - Liu, Yunchang; Xiang, Kaiqiang; Tian, Baozhu; Zhang, Jinlong
Abstract: The simultaneous discrimination of cysteine (Cys), homocysteine (Hcy) and glutathione (GSH) is of great importance due to their roles in biology and close link to many diseases, especially via the development of a far‐red fluorescent probe that could be used for rapid, selective, and sensitive detection of all three. Herein, we report the characterization of a far‐red fluorescent probe with turn‐on fluorescence properties and visible color changes that could be used for the detection of cysteine and homocysteine over glutathione. In this study we found that the sensor could discriminate cysteine and homocysteine over glutathione within 20 min. Function of this probe was based on the conjugate addition–cyclization reaction and showed a low detection limit to cysteine and homocysteine. Upon the addition of cysteine and homocysteine, the absorption band at 592 nm rose gradually and fluorescence was detected at 645 nm. The color changed from colorless to blue and fluorescence changed from absent to strong red fluorescence, which could be differentiated by the naked eye. All these unique features make this probe particularly potentially favorable for use in cysteine/homocysteine sensing and bioimaging applications. Copyright © 2016 John Wiley & Sons, Ltd.